Antifungal action of Ginger (Zingiber Offinale Roscoe) on Candida Albicans infection (Research, Society and Development, 2022)
The phytotherapy is an integrative therapy developed by the use of medical plants. In the variety of medical plants, the ginger (Zingiber Offinale Roscoe) is mostly used in popular medice due to its variety of therapeutics usages were scientific tested, standing out it’s antifungal potential and possibly usage in the candidiasis, which is an infection caused by Candida Albicans. In this perspective, the goal of this study was to analyze ginger’s therapeutics effects in the infection caused by C. albicans. The methodological aspects of this study are an integrative literature review with descriptive character and qualitative approach, that was made between February and April of 2022 using the National Center for Biotechnology Information (NCBI) and Literatura Latino-Americana e do Carie em Ciências da Saúde (LILACS) as data bases. To reach the articles in the data bases, it was used the following Descritores em Ciências da Saúde (DeCS): “Ginger” and “Antifungal” and “Candida Albicans”.  The studies showed a significantly positive relationship between the therapeutic usage of ginger’s extract (Z. Offininale) in the infection caused by Candida Albicans, indicating that phytotherapy as an effective alternative to candidiasis treatment. Besides this, the extract shows fewer adverse effects as an advantage when compared to synthetic medications to treat the disease.